Echocardiography Differentiates Lethally Irradiated Whole-Body From Partial-Body Exposed Rats - Inoue, Taeko; Zawaski, Janice A.; Sheehan, Vivien; Kanne, Celeste; Paikari, Alireza; Kaffes, Caterina C.; Sarkar, Poonam; Sabek, Omaima M.; Gaber, M. Waleed (Frontiers in Cardiovascular Medicine, 2018)
Background Acute radiation syndrome (ARS) affects morbidity and mortality dependent on the amount of body exposed. We propose the use of echocardiography (EC) to differentiate between survivors and non-survivors by measuring changes in cardiac function (CF) and pulmonary arterial function (PAF). We also investigate the role of rheology in our observed changes. Methods and Results Rats were irradiated to the whole body (WB) or partial body with two-legs shielded (2LS) at a lethal dose of 7.5Gy. EC and magnetic resonance imaging were performed, and rheological measurements conducted. Only 2LS survived past 12-days post-exposure and their CF and PAR were not significantly different from baseline. WB was significantly different from both baseline and 2LS in stroke volume (P<0.05), velocity time integral (VTI) (P<0.05) and pulmonary artery acceleration time (PAAT) (P<0.05). Differences were identified as early as six-days post-exposure, where VTI and PAAT were significantly (P<0.05) decreased in WB versus baseline but only PAAT was different from 2LS. Blood viscosity was significantly lower in the WB versus baseline and 2LS (P<0.0001). WB exhibited a significant rise in dense red blood cells versus baseline (P<0.01) and 2LS (P<0.01). Cell-free hemoglobin, a contributor to pulmonary artery hypertension and vasculopathy, was significantly elevated in WB versus sham. Conclusions Non-invasive and readily available imaging can be used to identify critically affected victims. Our findings point to heart failure as one possible cause of death in WB exposed animals, potentially exacerbated by rheological, hemolytic, and pulmonary factors, and the importance of developing radiomitigators against cardiac ARS mortality.